Strategic Planning in Public Secondary Schools in the Southern Governorates of Palestine and its Relationship to Competitive Advantage - Alghirbawi, Bahaa Darwish; Kuhail, Zenat Hamed; Al-Mozeyn, Sleman Hussein (Journal of Educational and Psychological Sciences, 2025)
The study aimed to identify the reality of practicing both strategic planning and competitive advantage in public secondary schools in the governorates of the Gaza Strip and the nature of the relationship between them from the teachers’ point of view. The researchers followed the descriptive analytical approach and used an electronic questionnaire as a research tool, on a stratified random sample of (357) teachers. The results showed that the research sample’s estimate of the degree of practicing strategic planning came with an overall average of (4.11), and the level of competitive advantage came with an overall average of (4.03), both with a (large) practice estimate. It was found that there were no statistically significant differences at the level (α≤0.05) between the average scores of the study sample members’ estimates of each of (the degree of practicing strategic planning, the level of competitive advantage) attributed to the variables (gender, educational level, years of service). It also showed a positive, direct correlation between the degree of practicing strategic planning and the level of competitive advantage, amounting to (0.91). Based on the results, the researchers recommended involving the local community and parents in the planning process to ensure that these plans respond to the needs of students and society, strengthening partnerships with international organizations to ensure the provision of funding for programs and activities in line with strategic plans, and investing in technology and its tools in planning processes. Strategic in light of limited resources and infrastructure challenges in the Gaza Strip.